Integration and School Inclusion in the brazilian bureaucratic-heritage historic panorama (Research, Society and Development, 2019)
The present study analyzes the insertion of students with specific educational needs in institutions of regular education, considering the characteristics of Brazilian society markedly patrimonial-bureaucratic. The methodologies used were documentary research, in relation to the current legislation that advocates attention to students with disabilities, global developmental disorders and high skills - Law 9,394 of December 20th, 1996; CNE / CEB Resolution No. 2 of September 11th, 2001; National Policy on Special Education in the Perspective of Inclusive Education 2008; Law No. 13,146, of July 6th, 2015 - and the bibliographic research of scientific productions concerning the matter addressed. As a result, it is considered that the legal regulations allow the inclusion of these students in the regular education system. However, this hybrid model of patrimonialism and bureaucracy, hinders substantial changes, because the attempt to implement inclusion in educational institutions, oppose traditional practices of teachers, maintaining the presuppositions of school integration. It is concluded that the continuous training of teachers, recommended by the legal regulations researched, creates the possibility of weakening pedagogical aspects rooted in heritage values, guaranteeing the effectiveness of school inclusion.